Distribution of 137Cs In the Surface Soil of Serpong Nuclear Site - E. Lubis (Atom Indonesia, 2011)
The distribution of 137Cs in the surface soil layer of Serpong Nuclear Site (SNS) was investigated by field sampling. The Objectives of the investigation is finding the profile of 137Cs distribution in the surface soil and the Tf value that can be used for estimation of radiation dose from livestock product-man pathways. The results indicates that the 137Cs activity in surface soil of SNS is 0.80 ± 0,29 Bq/kg, much lower than in the Antarctic. The contribution value of 137Cs from the operation of G.A.Siwabessy Reactor until now is undetectable. The Tf of 137Cs from surface soil to Panisetum Purpureum, Setaria Spha Celata and Imperata Cylindrica grasses were 0.71 ± 0.14, 0.84 ± 0.27 and 0.81 ± 0.11 respectively. The results show that value of the transfer factor of 137Cs varies between cultivated and uncultivated soil and also with the soils with thick humus. Received: 18 May 2010; Revised: 13 July 2011; Accepted: 20 July 2011